REFLECTIONS ON THE EXPERIENCE OF BOGOR CITY CULINARY SMEs IN BUILDING ORGANIZATIONAL COMMITMENT FOR BUSINESS SUSTAINABILITY - Elizabeth, Roosganda; Gursida, Hari; Moeins, Anoesyirwan; Yusnita, Nancy (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze how the experience of culinary SMEs in Bogor City plays a role in building organizational commitment that supports business sustainability. This study uses a qualitative approach with in-depth interview techniques with culinary SMEs in Bogor City. The results of the study indicate that the experience of business actors plays a very important role in decision making and business strategy planning. Experienced business actors tend to be better able to identify opportunities and challenges, and make the right decisions for the sustainability of their business. However, low managerial quality and high dependence on business owners are inhibiting factors in the formation of independent and sustainable organizations. This affects the ability of businesses to manage human resources and efficient operational processes. In addition, the study also revealed that business actors tend to under-utilize past experiences as a reflection for improvement, which can cause the same mistakes to be repeated. Therefore, the results of this study emphasize the importance of developing managerial skills, increasing reflection on past experiences, and effective human resource management to strengthen organizational commitment. All of these factors are very important to support the sustainability of culinary SMEs in Bogor City.